Wilm’s Tumor: Ten Year Experience at Kanti Children’s Hospital - Sah, Kailash Prasad; Rai, Ganesh Kumar; Shrestha, PN; Shrestha, Amit (Journal of Nepal Paediatric Society, 2010)
Introduction: Wilm's tumor is the second most common abdominal tumor in children. It arises from the kidney. The survival of children with Wilm's tumor has improved over the past 25 years. Objectives: To study the clinical presentation of Wilm’s tumor and evaluate the ten year survival. Materials and Methods: A retrospective hospital based study was conducted at Kanti Children's Hospital from March 1998 to February 2008. A total of 60 histopathologically diagnosed children below 14 yr of age were included in the study. Results: About 2/3rd (66.5%) presented with abdominal swelling followed by abdominal pain (16.5%) and fever (13.5%). A few children manifested with red colored urine (3.5%). The age of children ranged from one month to 13 years with the mean age of 36 months. Males were affected more than the females (M:F=3:1). Most affected age group was 2 to 5 yrs (41.5%) followed by 1 to 2 yrs (25.0%). Most of the cases were in stage III (36.5%) followed by stage II (33.5%). SIOP protocol was used to treat these children and overall 10 year survival rate was 50.0%. One fifth (20%) of the cases died, 16.5% relapsed and 13.5% lost to follow up. Conclusion: Despite severe resource limitations, paediatric oncology unit at Kanti Children’s Hospital has been successfully treating Wilm's tumor with the success rate of 50.0%. Key words: Chemotherapy; Outcome; Remission; Wilm’s tumor; SIOP. DOI: 10.3126/jnps.v30i2.3449 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 85-89